Selectivity and Activity of Iron Molybdate Catalysts in Oxidation of Methanol - Khalid Khazzal Hummadi (The Journal of Engineering Research, 2009)
The selectivity and activity of iron molybdate catalysts prepared by different methods are compared with those of a commercial catalyst in the oxidation of methanol to formaldehyde in a continuous tubular bed reactor at 200-350 oC (473-623 oK), 10 atm (1013 kPa), with a methanol-oxygen mixture fixed at 5.5% by volume methanol: air ratio. The iron(III) molybdate catalyst prepared by co-precipitation and filtration had a selectivity towards formaldehyde in methanol oxidation comparable with a commercial catalyst; maximum selectivity (82.3%) was obtained at 573oK when the conversion was 59.7%. Catalysts prepared by reacting iron (III) and molybdate by kneading or precipitation followed by evaporation, omitting a filtration stage, were less active and less selective. The selectivity-activity relationships of these catalysts as a function of temperature were discussed in relation to the method of preparation, surface areas and composition. By combing this catalytic data with data from the patent literature we demonstrate a synergy between iron and molybdenum in regard to methanol oxidation to formaldehyde; the optimum composition corresponded to an iron mole fraction 0.2-0.3. The selectivity to formaldehyde was practically constant up to an iron mole fraction 0.3 and then decreased at higher iron concentrations. The iron component can be regarded as the activity promoter. The iron molybdate catalysts can thus be related to other two-component MoO3-based selective oxidation catalysts, e.g. bismuth and cobalt molybdates. The iron oxide functions as a relatively basic oxide abstracting, in the rate-controlling step, a proton from the methyl of a bound methoxy group of chemisorbed methanol. It was proposed that a crucial feature of the sought after iron(III) molybdate catalyst is the presence of -O-Mo-O-Fe-O-Mo-O- groups as found in the compound Fe2(MoO4)3 and for Fe3+ well dispersed in MoO3 generally. At the higher iron(III) concentrations the loss of selectivity is due to the presence of iron oxide patches or particles which catalyze the total oxidation of methanol, and the loss of activity to blocking of molybdenum sites.